2022
DOI: 10.3390/en15197296
|View full text |Cite
|
Sign up to set email alerts
|

Boiling Heat Transfer Enhancement on Biphilic Surfaces

Abstract: Flat surfaces with different patterns of hydrophobic spots were employed for experimental investigation of boiling heat transfer. In one case, hydrophobic spots were created on a smooth copper surface and on a surface coated with arrays of micrococoons from silicon oxide nanowires by vapor deposition of a fluoropolymer. In the second case, a hydrophobic coating was deposited on heater surfaces with cavity microstructures formed by laser ablation and chemisorption of fluorinated methoxysilane. Water under satur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Chinnov et al. [ 48 ] have underscored the significance of the sustained and enduring boiling performance characteristics of manufactured biphilc coatings on boiling interfaces. This emphasis on longevity is a relatively infrequent aspect within the broader community of researchers in the field of boiling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Chinnov et al. [ 48 ] have underscored the significance of the sustained and enduring boiling performance characteristics of manufactured biphilc coatings on boiling interfaces. This emphasis on longevity is a relatively infrequent aspect within the broader community of researchers in the field of boiling.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation of the bubbles takes place in the hydrophobic areas, while the hydrophilic areas serve to prevent coalescence of the bubbles and provide liquid supply through wicking toward hydrophobic areas. Additionally, Chinnov et al [48] have underscored the significance of the sustained and enduring boiling performance characteristics of manufactured biphilc coatings on boiling interfaces. This emphasis on longevity is a relatively infrequent aspect within the broader community of researchers in the field of boiling.…”
Section: Introductionmentioning
confidence: 99%
“…The number of hydrophobic spots is 506 and 69, respectively, similar to the previous case. The elemental composition of these coatings was analyzed by the EDS method [8]. Thus, it was confirmed that the composition of the spots corresponds to the fluoropolymer, and there is no fluoropolymer in the space between the spots.…”
Section: Biphilic Surfaces With Fluoropolymer Spotsmentioning
confidence: 78%
“…It was concluded that both kinds of microstructures enhanced boiling due to agitated movement caused by evaporation as well as the rewetting process at bubble detachment. Chinnov et al [6] experimentally analyzed water boiling on heaters with different patterns of hydrophobic spots made on the copper surface as well as the surface covered with a matrix of micrococoons made of silicon oxide nanowires. It was reported that biphillic heaters showed better performance that non-biphillic ones.…”
Section: Introductionmentioning
confidence: 99%